'The troubles of collecting': William Henry Harvey and the practicalities of natural-history collecting in Britain's nineteenth-century world. Issue 1 (March 2022) - McAleer, John
Abstract: In recent decades, historians have become increasingly interested in the logistical challenges and difficulties encountered by those responsible for the collection, preservation and safe transport of specimens from the field to the museum or laboratory. This article builds on this trend by looking beyond apparent successes to consider the practices and practicalities of shipboard travel and maritime and coastal collecting activities. The discussion focuses on the example of William Henry Harvey, who travelled to Australia in pursuit of cryptogams – non-flowering plants like mosses, lichens and algae – in 1853. In his private correspondence to family and friends, Harvey offered insights into the challenges and obstacles faced by all collectors in the period. His experiences were fundamentally shaped by the material culture, embodied knowledge and physical constraints he encountered on the way. On one level, shipboard and onshore collecting activities were facilitated by the connections forged by new technologies and Britain's global empire. But they also depended on specific contexts and relied on local agents and actors, as well as on the physical and technical facilities (and limitations) of those doing the collecting. The examples of Harvey and others shed light on the real, 'lived' experiences of individual collectors, the difficulties and challenges they encountered in amassing their collections, and the networks of people on which they relied.